Monostiches of Yeghishe Charents - Grigoryan, Seyran (Բանբեր Երևանի համալսարանի. Բանասիրություն, 2021)
The article is dedicated to the monostiches of Yeghishe Charents. In 1937 the poet wrote 10 monostiches which were published in the 1970s-1980s. Charents mastered the single line form of the monostich with the help of Valery Bryusov, especially his translations of the monostiches of the 4th century Latin poet Decimus Magnus Ausonius. But genre traditions of ancient poetry and symbolism the Armenian poet used to embody his own ideas and designs.